2010
DOI: 10.1137/090756843
|View full text |Cite
|
Sign up to set email alerts
|

Krylov Subspace Methods for Linear Systems with Tensor Product Structure

Abstract: The numerical solution of linear systems with certain tensor product structures is considered. Such structures arise, for example, from the finite element discretization of a linear PDE on a d-dimensional hypercube. Linear systems with tensor product structure can be regarded as linear matrix equations for d = 2 and appear to be their most natural extension for d > 2. A standard Krylov subspace method applied to such a linear system suffers from the curse of dimensionality and has a computational cost that gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(173 citation statements)
references
References 18 publications
4
169
0
Order By: Relevance
“…The second approach has a drawback which will be discussed next. First we mention the following articles about conjugate gradient methods in the context of tensor methods: Tobler [29], Kressner-Tobler [23][24][25] , and Savas-Eldén [28].…”
Section: Cg-like Methodsmentioning
confidence: 99%
“…The second approach has a drawback which will be discussed next. First we mention the following articles about conjugate gradient methods in the context of tensor methods: Tobler [29], Kressner-Tobler [23][24][25] , and Savas-Eldén [28].…”
Section: Cg-like Methodsmentioning
confidence: 99%
“…In [83] it was shown that the matrix-vector product with the matrix (14) can maintain the low-rank structure, only requiring an additional truncation step that can be performed cheaply compared to the cost of the full method. The construction of such a truncation function T ε for the matrix case is further described in [46,83].…”
Section: Matrix Casementioning
confidence: 99%
“…As we noted, algebraic operations (matrix, scalar products and additions) and the SVD re-compression procedure in the TT format allow to rewrite any classical iterative method, keeping all vectors in the tensor format and performing only structured operations [64,4,21,46]. Let us denote the compression (or truncation) procedure from a vector y to a vector y ≈ y as y = T ε (y),…”
Section: Tensor Casementioning
confidence: 99%
“…The convergence of the Galerkin method on tensor products of (rational) Krylov subspaces for Lyapunov and Sylvester equations has been analysed in [2,10,21,20,27,28]. For the extensions considered in this paper the framework developed in [2] appears to be most suitable.…”
Section: Introductionmentioning
confidence: 99%
“…Such linear systems arise, for example, from the discretization of a separable d-dimensional PDE with tensorized finite elements [14,21]. Moreover, methods for (5) can be used as preconditioners in iterative methods for more general linear systems [19,4] and eigenvalue problems [22].…”
Section: Introductionmentioning
confidence: 99%